PENGARUH MODEL PEMBELAJARAN DISKURSUS MULTI REPRESENTASI TERHADAP HASIL BELAJAR SISWA MATERI HIMPUNAN - Domu, Ichdar; Pesik, Anekke; katiandagho, geofanny firsty (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. This research aims to examine the effectiveness of the DMR Learning Model in learning mathematics about set . The method used in this study as experiment.This research was conducted at SMP Negeri 1 Remboken in the odd semester of the 2019/2020 academic year. The subjects in the research were all class VII that will be taken 2 classes namely class VII c as control classÂ  and class VII Eas exsperiment clas. The results revealed that there were differences in the average learning outcomes of students taught using the DMR learning model higher than the average learning outcomes of students who were taught using the direct learning model, where the average student learning outcomes taught using the DMR learning model were 75, 58 higher than the average student learning outcomes taught using the direct learning model that is 61.83. Based on the above research results, it turns out learning by using the DMR learning model can affect improving student learning outcomes about the set. Â Keywords: Multi Representation Discourse, Learning Outcomes, Association